Juhudu al-Habib Hasan Bin Ahmad Baharun Fiy Ta’limi Maharoh al-Kalam Bima’had Dar al-Lughah Wa al-Da’wah Bangil Pasuruan - Masnun Masnun (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
ABSTRACT In the modern era, the people of many countries, young and old in the West and the East, realized the importance of learning other languages ​​besides the mother tongue, as the world became a small village with the advancement of technology and the explosion of knowledge. And speaking skill is considered an important skill in the process of language teaching, because the main goal in teaching a language today is the ability to speak. The objectives of this research are to reveal the efforts of Habib Hassan bin Ahmad Baharun in teaching the skill of speech at the Institute of Language and Da`wah at Bangil Pasuruan, which is considered one of the successful institutes in teaching this skill. This research used the qualitative design of the historical entrance. The data of this research were extracted from the interview, observation and documents were validated, proportionate and documented by the method of triangulation of data. This research produced discoveries about his efforts in developing the skill of speech, which are as follows: He wrote several books specifically to embody the skill of speech, and to intensify the linguistic environment by applying the skill of speaking, and holding lecture, theater and morning debate programs, and the formation of the language department. Keywords: efforts, education, skill of speech